2017
DOI: 10.1080/02670844.2017.1312739
|View full text |Cite
|
Sign up to set email alerts
|

Influence of carbide density on surface roughness and quasi-stable wear behaviour of H13 die steel

Abstract: Influence of cryogenic treatment on AISI H13 hot work die steels has been studied to correlate carbide density with surface roughness and dry sliding wear. This work includes hardening of AISI H13 specimens at 1020°C, oil quenching followed by double tempering at 500°C and then cryogenic treatment at −185°C for different cryosoaking periods from 8 to 32 h, followed by soft tempering at 100°C. The dry sliding wear behaviour on pin-on-disc has been studied for a load of 40 N at a speed of 3 m s −1 for the slidin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 15 publications
0
21
0
Order By: Relevance
“…It was reported that the optimum cryosoaking duration of 36 h to maximize hardness and to minimize the W R . The AISI H13 hot work tool steel (Fe-0.40C-0.30Mn-0.40Si-5.50Cr-1.40Mo-1.00V) hardened, oil quenched, double tempered and cryotreated by Shinde and Dhokey 12 . The cryosoaking duration was optimised at 16 h and at optimum cryosoaking duration highest carbide density, highest hardness, and lowest wear rate was reported.…”
Section: Analysis Of Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It was reported that the optimum cryosoaking duration of 36 h to maximize hardness and to minimize the W R . The AISI H13 hot work tool steel (Fe-0.40C-0.30Mn-0.40Si-5.50Cr-1.40Mo-1.00V) hardened, oil quenched, double tempered and cryotreated by Shinde and Dhokey 12 . The cryosoaking duration was optimised at 16 h and at optimum cryosoaking duration highest carbide density, highest hardness, and lowest wear rate was reported.…”
Section: Analysis Of Resultsmentioning
confidence: 99%
“…This is due to the availability of more alloying elements for nucleation and increased carbide nucleation during the warming up period up to 24 h cryosoaking period but beyond the 24 h cryosoaking time it slightly reduced. It may be due to the less availability of alloying elements 12,28 at the grain boundaries for nucleation of carbides which leads to the formation of coarse carbides by merging the smaller carbides. Due to the formation of coarse carbide beyond 24 h cryosoaking duration, the carbide density slightly gets reduced 29 .…”
Section: Microstructural Featurementioning
confidence: 99%
See 1 more Smart Citation
“…In this study, WDB620 (Figure 1) was selected as the material of the moving jaw plate, and then the ceramic powder was laser-cladded on the surface of the moving jaw plate. The contents of various chemical components of ceramic powder are shown in Table 1 [22][23][24][25]. The cylinder sample after cutting is installed on the friction electronic tester and closely contacts with the ring.…”
Section: Methodsmentioning
confidence: 99%
“…Some researchers have elaborated that the deep cryogenic treatment improves the surface finish of the materials through the refinement of martensite laths [19]. This method had been beneficial for materials such as AISI H13 die steel [20][21][22][23] in order to improve the wear resistance, hardness and surface characteristics, thereby enhancing the performance of the material.…”
Section: Introductionmentioning
confidence: 99%